Usage of L-type calcium channel blockers to suppress drug reward and memory driving addiction: Past, present, and future. (15th December 2022) - Morikawa, Hitoshi; Young, Cara C.; Smits, Jasper A.
Abstract: Over the past three decades, L-type Ca 2+ channel (LTCC) blockers have been considered a potential therapeutic drug to alleviate the symptoms of drug addiction. This idea has been supported, in part, by 1) expression of LTCCs in the brain dopaminergic circuits that are thought to play critical roles in the development and expression of addictive behaviors and 2) common usage of LTCC blockers in treating hypertension, which may enable off-label use of these drugs with good brain penetration as therapeutics for brain disorders. Addiction can be viewed as a maladaptive form of learning where powerful memories of drug-associated stimuli and actions drive compulsive drug intake. Largely under this framework, we will focus on the dopaminergic system that is thought be critically involved in drug-associated learning and memory and provide a brief overview of the past and recent studies testing the therapeutic potential of LTCC blockers for addictive disorders in animal models and humans and offer a future perspective on the use of LTCC blockers in drug addiction and, possibly, addiction to other non-drug rewards (e.g., gambling, eating, shopping). Interested readers can refer to other related articles in this issue and a comprehensive review available elsewhere (Little, 2021) to gain further insights into the roles of LTCCs in drug addiction and withdrawal symptoms associated with dependence. This article is part of the Special Issue on 'L-type calcium channel mechanisms in neuropsychiatric disorders'. Highlights: Off-label use of L-type calcium channel (LTCC) blockers for addiction. They may interfere with drug-induced conditioning and drug-associated memories. Development of LTCC blockers selective for the neuronal Cav1.3 subtype is critical. Potential use of LTCC blockers in combination with cue exposure therapy.